1997
DOI: 10.1091/mbc.8.12.2631
|View full text |Cite
|
Sign up to set email alerts
|

Accumulation of Major Histocompatibility Complex Class II Molecules in Mast Cell Secretory Granules and Their Release upon Degranulation

Abstract: To investigate the relationship between major histocompatibility complex (MHC) class II compartments, secretory granules, and secretory lysosomes, we analyzed the localization and fate of MHC class II molecules in mast cells. In bone marrow-derived mast cells, the bulk of MHC class II molecules is contained in two distinct compartments, with features of both lysosomal compartments and secretory granules defined by their protein content and their accessibility to endocytic tracers. Type I granules display inter… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

11
307
0
1

Year Published

1999
1999
2016
2016

Publication Types

Select...
4
4

Relationship

1
7

Authors

Journals

citations
Cited by 374 publications
(323 citation statements)
references
References 50 publications
(59 reference statements)
11
307
0
1
Order By: Relevance
“…These 'exosomes' appeared to play a central role in communication between lymphocytes and dendritic cells, mediating the development of cellular responses or suppressing excessive activation, as in AICD. The phenomena of shedding 'exosomes' have also been demonstrated with other haematopoietic cells, such as mast cells and platelets, and it is thought to play important roles mediating their actions (Raposo et al, 1997). Recent studies have isolated 'exosomes' from tumour cells in vivo and in vitro and have demonstrated the presence of tumourassociated antigens and class I MHC antigens (Wolfers et al, 2001;André et al, 2002a, b;Chaput et al, 2004).…”
Section: Discussionmentioning
confidence: 99%
“…These 'exosomes' appeared to play a central role in communication between lymphocytes and dendritic cells, mediating the development of cellular responses or suppressing excessive activation, as in AICD. The phenomena of shedding 'exosomes' have also been demonstrated with other haematopoietic cells, such as mast cells and platelets, and it is thought to play important roles mediating their actions (Raposo et al, 1997). Recent studies have isolated 'exosomes' from tumour cells in vivo and in vitro and have demonstrated the presence of tumourassociated antigens and class I MHC antigens (Wolfers et al, 2001;André et al, 2002a, b;Chaput et al, 2004).…”
Section: Discussionmentioning
confidence: 99%
“…During exocytosis, in addition to soluble proteins and mediators, vesicles heterogeneous in size and shape, termed exosomes, are released from the lumen of multivesicular bodies in the extracellular environment (3,4).…”
Section: Mast Cell-derived Exosomes Induce Phenotypic and Functional mentioning
confidence: 99%
“…Ag presentation by bone marrow-derived MCs (BMMC) is strictly controlled by cytokines: IL-4 and GM-CSF are potent inducers of the Ag-presenting capacity, whereas IFN-␥ completely abrogate this function. Thus, MCs synthesize MHC class II molecules, which accumulate in the internal membrane vesicles of multivesicular organelles called secretory granules (4). It has been recently shown that IL-4-treated BMMC and untreated MC lines P815 and MC/9 induce in vitro and in vivo B and T lymphocyte proliferation and cytokine production (17).…”
Section: Mast Cell-derived Exosomes Induce Phenotypic and Functional mentioning
confidence: 99%
“…14,20,21 It has been shown that various types of eukaryotic cells, including hematopoietic cells and more recently tumor cells, secrete exosomelike vesicles. [5][6][7][8][9][10][11][12][13] Exosomes have diverse functions on the basis of their origins. In particular, exosomes from B lymphocytes were found to stimulate CD4ϩ T cells in vitro and exosomes from tumor-peptide-pulsed dendritic cells could activate cytolytic T cells in vivo and induce an antitumor activity.…”
Section: Discussionmentioning
confidence: 99%
“…[1][2][3][4] These extracellular vesicles are also produced by various kinds of hematopoietic cells, including mast cells, platelets, T lymphocytes, B lymphocytes and dendritic cells (DCs), as well as by intestinal epithelial cells. [5][6][7][8][9][10][11][12][13] Exosomes are known to originate from the inward budding of limiting membrane of multivesicular bodies (MVBs), and these internal vesicles of MVBs are released into the extracellular space by fusion of MVBs with the plasma membrane. 14 Proteomic analysis of DC-or B-cell-derived exosomes revealed selective enrichment of a subset of cellular proteins, including antigen-presenting proteins such as MHC class I and II molecules, heat shock proteins (HSPs), targeting-related MFG-E8 and tetraspanins such as CD9, CD63, CD81 and CD82.…”
mentioning
confidence: 99%